Forty-five years of keratoprosthesis study and application at the Filatov Institute: a retrospective analysis of 1 060 cases - Stanislav Iakymenko (International Journal of Ophthalmology, 2013)
AIM: To present results of the keratoprosthesis method used at The Filatov Institute of Eye Diseases and Tissue Therapy.METHODS: A retrospective case series analysis was used to describe the development of new types of keratoprostheses and methods of implantation as well as different ways of leukoma strengthening.RESULTS: Keratoprosthesis was performed in 1 060 eyes of 1 040 patients with leukomas of different etiology: burns, 725 eyes (68.4%); trauma, 120 eyes (11.3%); keratitis and ocular pemphigoid, 108 eyes (10.2%); and bullous keratopathy, 107 eyes (10.1%). Visual acuity before keratoprosthesis consisted of light perception in 962 eyes (92%), and 98 eyes (8%) had minimal visual acuity (1/200-1/50). Both eyes were blind (visual acuity less than 1/200) in 955 patients (91.8%). The period of blindness varied from 1 to 52 years. As a result of keratoprosthesis, visual acuity of ≥1/200 was restored in 1 023 of 1 060 eyes (96.5%). Visual acuity of 20/200-20/20 was achieved in 716 eyes (67.5%). At the last follow-up visit visual acuity of ≥1/200 was preserved in 806 eyes (76%), visual acuity of 20/200-20/20 was measured in 583 of 1 060 eyes (55%) and good keratoprosthesis fixation in the cornea was achieved in 986 of 1 060 eyes (93%). The minimal follow-up was 12 months (range, 12 months to 37 years, median 5 years).CONCLUSION: Our techniques of keratoprosthesis effectively restore vision in patients with leukomas that cannot be treated by optical corneal grafting.